A new phenomenological-based rate-dependent hysteresis operator for hysteresis characterization / Mohd Hanif Mohd Ramli and Mohd Azuwan Mat Dzahir - Mohd Ramli, Mohd Hanif; Mat Dzahir, Mohd Azuwan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Hysteresis is a fundamental problem in most smart material based actuators. This phenomenon limits the performance of systems that driven by these actuators. Therefore, there is a need for a comprehensive and robust approach to model and control in order to eliminate the hysteresis effects. This paper presents an alternative modification to the original Bouc-Wen (BW) model so as to improve the characterization of smart actuators those are affected by hysteresis nonlinearity. For this purpose, an extended BW (EBW) model is proposed and formulated in the discrete-time domain. Due to nonlinear nature of the proposed model, an extended particle swarm optimization technique (EPSO) is used to properly validate EBW model. Through the simulation study, it is observed and confirmed that proposed model is capable of describing rate-dependent input-output relations, which is an important feature in the modeling of hysteresis phenomenon.